Keterbukaan Informasi Publik Data Pertanahan - Nur Rahmanto (Sekolah Tinggi Pertanahan Nasional, 2021)
In essence, every citizen has the right to know about all activities or policies carried out by public officials, this is in addition to the right to obtain information, it is a human right as well as a means of public control over government administration, but the right to obtain this information is often There are obstacles both in terms of regulations and unsupportive behavior of public officials. Law Number 14 of 2008 (UU KIP) which regulates the issue of public information disclosure in its implementation conflicts with Permenagraria / Ka BPN Number 3 of 1997, in which the regulation of the Minister of State for Agrarian Affairs regulates restrictions on restrictions in providing information on land data which are often inconsistent with with the regulation of public information disclosure regulated in the KIP Law, so that the public does not immediately get information on land data which in turn will lead to a lawsuit from the public to the Ministry of Agrarian Affairs and Spatial Planning / BPN at the Information Commission and State Administrative Court. By using the desk study method, this paper will examine the information disclosure arrangements stipulated in the two regulations referred to as well as the conflicts that occur both in the articles of the contents of the regulations and in their implementation practices so that solutions or recommendations will be obtained so that public information disclosure can run properly in Indonesia country.Keywords: public information disclosure, data sharing, land data . Intisari: Setiap warga masyarakat pada hahekatnya adalah berhak untuk tahu mengenai semua kegiatan atau kebijakan yang dilakukan oleh pejabat publik, hal ini selain hak untuk memperoleh informasi itu adalah hak asasi setiap manusia juga sebagai sarana kontrol publik terhadap penyelenggaraan pemerintahan, akan tetapi hak untuk memperoleh informasi ini sering ada kendala baik dari sisi regulasi maupun perilaku petugas publik yang tidak mendukung. Undang Undang Nomor 14 Tahun 2008 (UU KIP) yang mengatur masalah keterbukaan informasi publik dalam pelaksanannya berbenturan dengan Permenagraria/Ka BPN Nomor 3 Tahun 1997, dimana di dalam peraturan Menteri Negara Agraria dimaksud diatur mengenai pembatasan pembatasan dalam memberikan informasi data pertanahan yang seringkali tidak sejalan dengan pengaturan keterbukaan informasi publik yang diatur di dalam UU KIP, sehingga masyarakat tidak serta merta bisa mendapatkan informasi data pertanahan yang pada akhirnya akan memunculkan gugatan dari masyarakat kepada Kementerian Agraria dan Tata Ruang/BPN di Komisi Informasi dan Pengadilan Tata Usaha Negara. Dengan menggunakan methode desk study tulisan ini akan mengkaji pengaturan keterbukaan informasi yang diatur di dalam kedua peraturan dimaksud serta pertentangan yang terjadi baik di dalam pasal pasal isi peraturan maupun di dalam praktek pelaksanaannya untuk selanjutnya akan diperoleh solusi atau rekomendasi sehingga keterbukaan informasi publik dapat berjalan dengan baik di Negara Indonesia.Kata Kunci: keterbukaan informasi publik, berbagi data, data pertanahan.